Fresh Lipstick: Redressing Fashion and Feminism - Scott, L (Palgrave Macmillan, 2005)
Linda M. Scott wants to put an end to the belief that American women have to wear a colorless, shapeless uniform to achieve liberation and equality. A pointed attack on feminism's requisite style of dress, Fresh Lipstick argues that wearing high heels and using hair curlers does not deny you the right to seek advancement, empowerment, and equality. Scott asserts that judging someone on her fashion choices is as detrimental to advancement as judgments based on race, nationality, or social class. Fashion is an important mode of personal expression, not an indication of submission. She demonstrates that feminism's dogged reduction of fashion to sexual objectification has been motivated by a desire to control other women, not free them. This push for power has produced endless conflict from the movement's earliest days, hindering advances in women's rights by promoting exclusion. It is time for the "plain Jane" dress code of the revolution to be lifted, allowing all women to lead, even those wearing makeup and Manolos.